Anioł i syn – językowy portret Stanisława Witkiewicza-ojca - Majewska-Wójcik, Anna Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In the article the Stanisław Witkewicz`s figure is presented from the perspective of one of his private roles – the father role. The items discussed in the paper concern relations between the father and the only son Stanisław Ignacy, what way Witkacy the son was perceived by the father, and what were Witkewicz`s priority parental rules which he was governed by in his only child`s upbringing. The analysis are made on the grounds of the letters from Witkiewicz to his son and another family correspondence, and the article is the continuation of the subject originated by Małgorzata Król who has studied the personas of Wincenty Pol and Gustaw Zieliński in such a context.